Real-Time Detection of Riboflavin Production by Lactobacillus plantarum Strains and Tracking of Their Gastrointestinal Survival and Functionality in vitro and in vivo Using mCherry Labeling - Mohedano, Mari Luz; Hernández-Recio, Sara; Yépez, Alba; Requena, Teresa; Martínez-Cuesta, M. Carmen; Peláez, Carmen; Russo, Pasquale; LeBlanc, Jean Guy; Spano, Giuseppe; Aznar, Rosa; López, Paloma (Frontiers in Microbiology, 2019)
Some strains of lactic acid bacteria (LAB) produce riboflavin, a water-soluble vitamin of the B complex, essential for human beings. Here, we have evaluated riboflavin (B2 vitamin) production by five Lactobacillus plantarum strains isolated from chicha, a traditional maize-based fermented alcoholic beverage from north-western Argentina and their isogenic riboflavin-overproducing derivatives previously selected using roseoflavin. A direct fluorescence spectroscopic detection method to quantify riboflavin production in bacterial culture supernatants has been tested. Comparison of the efficiency for riboflavin fluorescence quantification with and without prior HPLC fractionation showed that the developed method is a rapid and easy test for selection of B2 vitamin-producing strains. In addition, it can be used for quantitative detection of the vitamin production in real time during bacterial growth. On the basis of this and previous analyses, the L. plantarum M5MA1-B2 riboflavin overproducer was selected for in vitro and in vivo studies after being fluorescently labelled by transfer of the pRCR12 plasmid, which encodes the mCherry protein. The labelling did not affect negatively the growth, the riboflavin production nor the adhesion of the strain to Caco-2 cells. Thus, L. plantarum M5MA1-B2[pRCR12] was evaluated for its survival under digestive tract stresses in the presence of microbiota in the dynamic multistage BFBL gut model and in a murine model. After exposure to both models, M5MA1-B2[pRCR12] could be recovered and detected by the pink color of the colonies. The results indicated a satisfactory resistance of the strain to gastric and intestinal stress conditions but a low colonization capability observed both in vitro and in vivo. Overall, L. plantarum M5MA1-B2 could be proposed as a probiotic strain for the development of functional foods.